Mapping the Intellectual Landscape of Multidisciplinary Research: A Bibliometric Analysis of the NPRC Journal of Multidisciplinary Research from Inception to Present - Shrestha, Hira Lal; Regmi, Pratiksha; Gurung, Sajana; Lama, Sumina (NPRC Journal of Multidisciplinary Research, 2025)
Background: Multidisciplinary research plays a vital role in tackling various complicated modern-day problems. Specialized journals, such as the NPRC Journal of Multidisciplinary Research, act as the main platform for disseminating this type of scholarship. To date, there has been no comprehensive or quantitative study carried out on its publication landscape and scholarly impact. Objectives: The present study carries out a foundational bibliometric analysis of NPRC-JMR from its inception to the present. Its specific objectives are to identify the most prolific authors, map their collaborative networks, and delineate the intellectual structure and predominant research themes. Methods: A full bibliometric dataset was obtained from the lens.org database on 15th September 2025. After cleaning the data systematically, records were analyzed with the help of software such as wordsift and VOSviewer. In this method, performance analysis, co-authorship analysis, keyword co-occurrence analysis, and themes are included. Results: The analysis shows the steady rise in annual output of the journal, with contributions from a truly diverse global author base. Key research themes identified include "sustainable development" and "educational technology". Social network analysis revealed high levels of international collaborations, especially between institutions. Novelty/Conclusion: This research presents the first consolidated bibliometric profile of NPRC-JMR, providing an evidence-based retrospective of its development and intellectual structure. These findings have useful implications for the journal’s editors and publishers in terms of their strategy, and provide a guide for potential authors in the form of established research fronts and collaborative opportunities. The present analysis sets a milestone for the further development of the journal and underlines its position within the multidisciplinary research network.